Parental Communication On Sexual Reproductive Health In Adolescents - Vera Pujiyati; Noveri Aisyaroh (Jurnal Maternitas Kebidanan, 2026)
Adolescents (10–19 years) are a vulnerable group to sexual and reproductive health problems, including risky sexual behavior, unintended pregnancy, sexually transmitted infections (STIs), and HIV/AIDS. Limited sexual communication between parents and adolescents—due to cultural barriers, feelings of embarrassment, and parents' lack of knowledge—may increase these risks. This literature review aims to analyze the relationship between parent–adolescent communication and adolescents' sexual and reproductive health. The method used was a literature review by searching articles published between 2022 and 2026 in Google Scholar and PubMed using keywords related to adolescents, parental communication, and reproductive health, resulting in 10 articles analyzed narratively. The findings show that parent–adolescent communication about Sexual and Reproductive Health (SRH) remains low in several studies (<40–50%); However, open and effective communication is associated with improved adolescent knowledge and reduced risky sexual behavior. In conclusion, parental communication plays an important protective role in promoting adolescents' sexual and reproductive health, highlighting the need to improve parents' SRH education and communication skills.